Perinatal Western Diet Consumption Leads to Profound Plasticity and GABAergic Phenotype Changes within Hypothalamus and Reward Pathway from Birth to Sexual Maturity in Rat - Paradis, Julie; Boureau, Pierre; Moyon, Thomas; Nicklaus, Sophie; Parnet, Patricia; Paillé, Vincent (Frontiers in Endocrinology, 2017)
Perinatal maternal consumption of energy dense food increases the risk of obesity in children. This is associated with an overconsumption of palatable food that is consumed for its hedonic property. The underlying mechanism that links perinatal maternal diet and offspring preference for fat is still poorly understood. In the present study we aim at studying the influence of maternal high-fat/ high-sugar diet feeding (western-diet, WD) during gestation and lactation on the reward pathways controlling feeding in the rat offspring from birth to sexual maturity. We performed a longitudinal follow-up of WD and Control offspring at three critical time periods (childhood, adolescence and adulthood) and focus on investigating the influence of perinatal exposure to palatable diet on i) fat preference, ii) gene expression profile and iii) neuroanatomical/architectural changes of the mesolimbic dopaminergic-networks. We showed that WD feeding restricted to the perinatal period has a clear long lasting influence on the organization of homeostatic and hedonic brain circuits but not on fat preference. We demonstrated a period specific evolution of the preference for fat that we correlated with specific brain molecular signatures. In offspring from WD fed dams we observed during childhood the existence of fat preference associated with a higher expression of key gene involved in the DA-systems; at adolescence, a high fat preference for both groups, progressively reduced during the 3 days test for the WD group and associated with a reduced expression of key gene involved in the DA-systems for the WD group that could suggest a compensatory mechanism to protect them from further high fat exposure; and finally at adulthood, a preference for fat that was identical to control rats but associated with profound modification in key genes involved in the GABA network, serotonin receptors and PSA-NCAM dependent remodeling of the hypothalamus. Altogether these data reveal that maternal WD, restricted to the perinatal period, has no sustained impact on energy homeostasis and fat preference later in life even though a strong remodeling of the hypothalamic homeostatic and reward pathway involved in eating behavior occurred. Further functional experiments would be needed to understand the relevance of these circuits remodeling.